Հին Հայերենի խուլ հպականների հնչաբանական բնութագրերը (համաժամանակյա եւ տարաժամանակյա քննություն) - Վարդան Պետրոսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Древнеармянский язык, как и древнеиндийский, является одним из индо-европейских языков, который различал две фонемные серии глухих смычных: придыхательные и непридыхательные. The old Armenian language, like the old Indian, is one of the Indo-European languages that differentiates between two phonemic categories of occlusives — voiced and voiceless.
Keywords: Philology; Linguistics; Language and Literature